After the sunset - Ratner, Brett
Two master thieves. Max Burdett (Pierce Brosnan) and his beautiful accomplice Lola, (Salma Hayek) have escaped to the Bahamas to relax and enjoy their hard-earned riches. But Stan (Woody Harrelson), the FBI agent trailing Max, refuses to believe that his nemesis is calling it quits. He suspects Max and Lola of plotting to steal the last Napoleon diamond, coincidentally scheduled to arrive on the island as part of a cruise ship exhibition. While Lola is content settling into their new life of leisure. Max contemplates stealing the diamond. Now the question is will he get back into the heist game- and will Stan finally catch him? After the Sunset is a high-stakes, action thrill ride with mile-a-minute twists that will leave you breathless!